Export of organic matter, sulphate and base cations from boreal headwater catchments downstream to the coast : impacts of land use and climate - Mattsson, Tuija (Finnish Environment Institute, 2013)
The terrestrial export of dissolved organic matter (DOM) is associated with climate, vegetation and land use, and thus is under the influence of climatic variability and human interference with terrestrial ecosystems, their soils and hydrological cycles. The present study provides an assessment of spatial variation of DOM concentrations and export, and interactions between DOM, catchment characteristics, land use and climatic factors in boreal catchments. The influence of catchment characteristics, land use and climatic drivers on the concentrations and export of total organic carbon (TOC), total organic nitrogen (TON) and dissolved organic phosphorus (DOP) was estimated using stream water quality, forest inventory and climatic data from 42 Finnish pristine forested headwater catchments, and water quality monitoring, GIS land use, forest inventory and climatic data from the 36 main Finnish rivers (and their sub-catchments) flowing to the Baltic Sea. Moreover, the export of DOM in relation to land use along a European climatic gradient was studied using river water quality and land use data from four European areas. Additionally, the role of organic and minerogenic acidity in controlling pH levels in Finnish rivers and pristine streams was studied by measuring organic anion, sulphate (SO4) and base cation (Ca, Mg, K and Na) concentrations. In all study catchments, TOC was a major fraction of DOM, with much lower proportions of TON and DOP. Moreover, most of TOC and TON was in a dissolved form. The correlation between TOC and TON concentrations was strong and TOC concentrations explained 78% of the variation in TON concentrations in pristine headwater streams. In a subgroup of 20 headwater catchments with similar climatic conditions and low N deposition in eastern Finland, the proportion of peatlands in the catchment and the proportion of Norway spruce (Picea abies Karsten) of the tree stand had the strongest correlation with the TOC and TON concentrations and export. In Finnish river basins, TOC export increased ...